Knowledge, perceptions, and interest of referring physicians regarding the implementation of Artificial Intelligence in CT Imaging in the Democratic Republic of Congo - Tacite Kpanya Mazoba; Benjamin Bofengu Lombo; Gertrude Mvila Luyeye; Jean Tshibola Mukaya; Antoine Aundu Molua (Orapuh Journal)
Introduction